Scientific inquiry learning with a simulation: providing within-task guidance tailored to learners' understanding and inquiry skill. Issue 6 (13th April 2022) - Fukuda, Mari; Hajian, Shiva; Jain, Misha; Liu, Arita L.; Obaid, Teeba; Nesbit, John C.; Winne, Philip H.
ABSTRACT : In scientific inquiry learning, within-task guidance tailored to the learner's domain knowledge and inquiry skill may be essential to promote intended learning outcomes. However, due to dynamic complexity across the timeline of inquiry learning, principles for designing tailored guidance are elusive. In this study, experienced tutors provided just-in-time guidance to 11 learners. We analysed tutor-learner interactions to investigate how tutors adapted guidance. We found tutors provided five types of guidance: prompts, support for domain knowledge, assessments, hints, and feedback. Guidance was provided when learners made errors, expressed difficulties, or asked questions; or when the tutor judged a learner successfully demonstrated a skill and was ready to progress to a follow-on skill. Based on these results, we propose a model for tailored, just-in-time guidance in simulation-assisted inquiry learning environments.